"It's safe to come, we've got lattes": Development disparities in Detroit. (February 2017) - Reese, Laura A.; Eckert, Jeanette; Sands, Gary; Vojnovic, Igor
Highlights: This paper considers two related questions about Detroit's trajectory: Does the current positive image of Detroit reflect reality?; and, Will the recovery culminate in a new Detroit that will provide residents with a quality of life that is sustainable in the decades to come? While the record is complex, two major conclusions stand out: 1) on a number of measures, Detroit continues to decline and, even when positive change has occurred, growth has been much less robust than many narratives would suggest. 2) Within the city, recovery has been highly uneven, resulting in increasing inequality. The gap between Detroit's core area (Downtown and Midtown) and its neighborhoods is significant and increasing. Unless there is a significant commitment to improving education and job skills throughout Detroit, the gap between the core and neighborhoods will continue to widen.